Testing the Moderating Effect of Gender on Job Satisfaction and Employees’ Behaviours Relationship: Evidence from Mobile Telecommunication Network (MTN) Buea, Cameroon - Nwahanye Emmanuel; Atabong Nkeng Lionel Agaha (European Scientific Journal, ESJ, 2021)
With the quest of personalization of actions from their employees, organisations are constantly looking for means that allow them to consider all employees’ needs in designing satisfaction tools that will enable their employees to portray adequate behaviours at work. The present study explored whether gender moderates the relationship between job satisfaction and employees’ behaviours within a telecommunication company in Cameroon (MTN, Buea). A quantitative cross-sectional method was used with a sample size of 212 respondents. The hierarchical moderated regression and the multigroups regression approach were used as data analysis tools. Findings showed that gender moderates the effect of job satisfaction on employees’ commitment and employees’ citizenship behaviour. It is a quasi-moderation and the size effect is characterized as low. Contrariwise, gender does not moderate the effect of job satisfaction on employees’ intention to quit. These findings can help inform intervention efforts by identifying gender-fit job satisfaction tools and policies to optimize the adoption by each group of adequate behaviours in the company.